The Contribution of Linguistic Typology to the Study of Biblical Hebrew in Africa: The Case of Pronouns in Sesotho : “Theoretical Approaches to Anaphora and Pronouns in Biblical Hebrew”: Papers forming part of the 2017 SBL Linguistics and Biblical Hebrew Seminar (Boston, USA) - Makutoane, Tshokolo J. (Journal for Semitics, 2020)
African languages and linguistic communities differ in many respects from their Western counterparts. As a result, the standard philological resources available to African scholars of Biblical Hebrew are often inadequate for understanding Biblical Hebrew and for conveying the meaning and function of Hebrew terms and constructions in African languages and societies. This article is based on linguistic typology, which deals with the examination of linguistic features across languages. It compares pronouns in Sesotho to pronouns in Biblical Hebrew and examines their similarities and differences. The purpose of the comparison is to demonstrate how the relevant features of Biblical Hebrew pronouns can be communicated effectively to Sesotho students by determining how the two languages’ pronoun systems correspond to one other typologically.